HUMAN COURAGE AND DIGNITY IN ERNEST J. GAINS’ A LESSON BEFORE DYING - Simamora, Rosa Maria; Pangaribuan, Jontra Jusat; Rumapea, Linus (Universitas Katolik Santo Thomas Medan, 2022)
This research is of human courage and dignity in Ernest J. Gaines’s novel, A Lesson Before Dying. People are able to face threat, pain, danger, or even death in order to maintain their right and dignity relying on courage. This is library research and applies mimetic criticism proposed by Abrams saying that a work of literature is the imitation of the real world. It depicts human beings who struggle to maintain and get acknowledgement of their right and dignity to live respectfully and worthly. The analysis is focused on how courage and dignity have raised someone from desperation into brave and thoughtful to face his death. He is desperated because of a false accusision of being a murderer, compared as a hog, and sentenced to die in electric chair. Comparing to a hog makes him lost his courage and self-esteem. He alienates himself and does not want to speak to anybody, but his godmother disagrees so she begs a teacher to teach him that he is a human being and should die as a human being too. He is taught by a teacher of moral and obligation to face his death courageously and shows that he is a human being who has duty and responsibility. Finally, he is able to sacrifice his death as a symbol of his courage and dignity to himself, his family and community. It is found that the author Ernest J Gains vividly conveys human beings who have courage are able to maintain and get acknowledgement of their right and dignity although they have to face threat, pain, danger, or even death.